The origin of the third-millennium BC fine grey wares found in eastern Arabia - Méry, Sophie; Besenval, Roland; Blackman, Michael James; Didier, Aurore (Proceedings of the Seminar for Arabian Studies, 2012)
From 2600 BC to c.2100-2000 BC, during the Umm an-Nar period, the pottery assemblages of eastern Arabia present numerous and varied affinities with those of Kech Makran and the assemblages of the Iranian regions of Kermān (Kirmān) and Sīstān. The results of neutron activation and thin-section analyses of samples of pottery show that the composition of the productions from the Dasht in Kech Makran (province of Balochistān, Pakistan) is similar to that of most of the ’Emir’ style pottery from Umm an-Nar sites, which was previously tested. This applies mainly to the fine grey painted or incised wares.